A novel control mechanism for hybrid 5-level DC-DC converter for higher switching frequency and lower voltage ripple - Mazloum, Mohamed Samir (AUC Knowledge Fountain, 2017)
The introduction and development of hybrid DC-DC converters present a valuable opportunity in on-chip power management, as they combine the advantages of buck and switched-capacitor converters while alleviating shortcomings such as conversion efficiency and sizing requirements. In this paper, a new control methodology is presented for the recently developed 5-level hybrid DC-DC converter, which utilizes the Virtex 5 LX50T FPGA to drive the converter. This control method allows for a higher switching frequency of 1MHz and an improved conversion efficiency while also allowing for dynamic voltage control based on the desired output voltage. Simulations as well as a test circuit are used to illustrate the proper control functionality, with tabulated results that showcase the efficiency advantage over prior control methods as well as the buck and 3-level hybrid converters.